Penggunaan Software Cisco Packet Tracer Dalam Simulasi Jaringan Seluler Pada Pembelajaran Materi Terminal Telkomunikasi - Yunita Yunita; Muhammad Aziz Nur Mubarok; Arjuna Fikri Tri Firmansyah; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Cellular networks play an important role in modern life with the availability of flexible connectivity in various places, fast internet access and communication services and are a reference for innovation and economic growth. However, the complexity of cellular networks requires careful planning and management, this is to ensure a reliable and safe service. The method used in designing cellular networks is the simulation method, namely by using Cisco Packet Tracer software and literature studies from various references. The results of cellular network simulations using this software can show superiority in designing, configuring and testing cellular networks. Apart from that, this software also provides complete features to meet several needs, starting from the process of creating a network topology, configuring IP addresses, activating DHCP services and HTTP services, to testing connections using PDU samples between smartphone devices and servers. With the successful connection test, it can be concluded that the settings and services on the cellular network have been tested and verified using Cisco Packet Tracer. This has shown that the software used is very effective in simulating and testing cellular networks.